2011
DOI: 10.1186/1751-0759-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Fulfillment of the premenstrual dysphoric disorder criteria confirmed using a self-rating questionnaire among Japanese women with depressive disorders

Abstract: BackgroundSome women with depressive disorders experience severe premenstrual symptoms. However, there have been few studies in which premenstrual symptoms in women suffering from depressive disorders were assessed. In this study, we aimed to investigate premenstrual symptoms in women with depressive disorders using the premenstrual dysphoric disorder (PMDD) scale.MethodsWe administered questionnaires to 65 Japanese female outpatients who had been diagnosed with a major depressive disorder or dysthymic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
3
28
1
1
Order By: Relevance
“…In the present study the prevalence of PMDD among students in year of 2015 was 26.8% which was similar with the study conducted in Ethiopia, Jimma [18]. But it is higher than other studies conducted in Saudi Arabia 22.4% [22], Iran 16.9% [23], Germany 5.8% [24] and Pakistan 5.8% [25]. However, the finding of the present study was lower than from other studies such as Iran 59% [26], Japanese 43% [27] Nigeria 36.1% [28,29].…”
Section: Magnitude Of Premenstrual Dysphoric Disordersupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study the prevalence of PMDD among students in year of 2015 was 26.8% which was similar with the study conducted in Ethiopia, Jimma [18]. But it is higher than other studies conducted in Saudi Arabia 22.4% [22], Iran 16.9% [23], Germany 5.8% [24] and Pakistan 5.8% [25]. However, the finding of the present study was lower than from other studies such as Iran 59% [26], Japanese 43% [27] Nigeria 36.1% [28,29].…”
Section: Magnitude Of Premenstrual Dysphoric Disordersupporting
confidence: 88%
“…All students had experience of menstruating at mean age of 13.66 (± 1.5) years (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The majority 326 (72.8%) had regular menstrual cycle while 193 (37.2%) had irregular menstrual cycles.…”
Section: Obstetrics and Gynecological Factorsmentioning
confidence: 99%
“…Part two asked about the effect of premenstrual symptoms on work and social life. Participants were asked to indicate ('yes' or 'no') whether a premenstrual symptoms interfere with housework, relationships with co-workers, family members, friends and acquaintances, part one and two were adapted from other similar studies (Miyaoka et al, 2011;Hamaideh et al, 2014;Hammam et al, 2012). Finally, participants are asked to respond ('yes' with score =1 or 'no' with score= 0) as to whether premenstrual symptoms "psychological, behavioural, physical" affect their work capacity, their ability to cope at work and whether they felt their employed work make their symptoms worse and then total score ranging from (0 to 20, the total number of symptoms that could affect these variables) was calculated for each variable according to the positive answers they report.…”
Section: -Study Methodsmentioning
confidence: 99%
“…Previous studies have confirmed the validity and reliability of the Japanese PMDD scale. 21,22 The NRS used in this study was an 11-point scale used to assess general health status on the day the scale was completed, from 0 (the worst of your life) to 10 (the best of your life).…”
Section: Measurementsmentioning
confidence: 99%